TAILORING LUXURY RETAIL STRATEGIES Exploring Consumer Needs in the Swedish Market - Bonnier Eklund, Elise; Ravegård, Linnea (My University, 2025)
As consumer heterogeneity grows, firms in the Swedish luxury industry face increasing challenges in responding to the distinct preferences of emerging generational cohorts, particularly Generation Z, while retaining the loyalty of traditional consumers such as Generation X. Due to the conservative nature of the luxury sector, characterized by institutional inertia and resistance to change, response to shifts in the industry is often slow and cautious. Existing research on generational differences in luxury consumption has largely focused on international markets, leaving the Swedish context underexplored. This study investigates how Generation X and Generation Z consumers in Sweden perceive luxury, what motivates their luxury purchases, and how they navigate the luxury customer journey. Drawing on 24 exploratory and 10 in-depth semi-structured interviews, the findings reveal that Generation X views luxury through a product-centric lens, emphasizing quality, durability, and heritage. In contrast, Generation Z consumers perceive luxury more aesthetically and symbolically, often associating it with peer validation, indulgence, and as a sustainable alternative to fast fashion. The study identifies clear differences in generational customer journey behaviors, with Generation Z favoring digital engagement and seamless transitions across channels, while Generation X values physical experiences and longer-term relationships. A distinctly Swedish perspective also emerged, such as understatement and Scandinavian aesthetic. Based on these insights, the study proposes three strategic focus areas for luxury firms: Locally tailored assortment, Personalizing for loyalty, and Seamless customer journeys. Together, these provide a roadmap for shifting from traditional luxury strategies to a more customer- centric approach that aligns with generationally diverse expectations of luxury.
Keywords: luxury; conservative industry; generational cohorts; customer journey; luxury strategy